Entre el saber y el aula, una responsabilidad ética, política y moral - Bonilla Campo, Constanza (Universidad Santiago de Cali, 2020)
Training in teaching practice exercises are subject to complex patterns of cultural intervention that can reach even up to the cultural symbolic violence. This document gives an account of the tensions over the practice of teacher training students of the Bachelor of performing in infancy in some children's homes of the Colombian Institute of family welfare in the city of Popayan. A city of colonial and traditional, but receiving roots of large contingents of people with different cultural complexion, ethnic and victimized by the armed conflict. The narrations recreate virtually these tensions. For this purpose, we used educational ethnography, seeking to reveal situations lived in the school context in tension with the Cauca culture. Indeed, by observing participant and the categorization of field diaries found a series of goal stories that survive in school, and who realize the learning processes outside of official discourse. Finally, is it brings to intervention design in the teaching activities and research in the classroom, giving account of the heterogeneity of the minor children, which involves also rethinking the didactic and pedagogic, model towards horizons metodològic you, who recognize the origin of learners and their characteristic identity Indeed, by observing participant and the categorization of field diaries found a series of goal stories that survive in school, and who realize the learning processes outside of official discourse. Finally, is it brings to intervention design in the teaching activities and research in the classroom, giving account of the heterogeneity of the minor children, which involves also rethinking the didactic and pedagogic, model towards horizons metodologic you, who recognize the origin of learners and their characteristic identity